2011
DOI: 10.1039/c1jm11870f
|View full text |Cite
|
Sign up to set email alerts
|

Diarylethene-based photochromic polyurethanes for multistate optical memories

Abstract: Photochromic polyurethanes (PPUs) are synthesised by reaction between a diarylethene end-capped with hydroxyl groups and an aliphatic diisocyanate. In situ polymerisation provides amorphous films with remarkable optical properties. The possibility to vary the amount and the chemical structure of the photochromic monomer without affecting the reactivity of the polymerization allows one to tune in a wide range the optical properties of these films. In addition, different diarylethenes can be mixed together to gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 57 publications
(55 reference statements)
0
39
0
Order By: Relevance
“…403 Figure 29, and readout nondestructively using a 1064 nm laser, which does not induce any photochromic reaction, as the excitation line source. The setup used for the readout is shown in Figure 30.…”
Section: Infrared (Ir) Absorption Raman Scattering and Refractive Imentioning
confidence: 99%
“…403 Figure 29, and readout nondestructively using a 1064 nm laser, which does not induce any photochromic reaction, as the excitation line source. The setup used for the readout is shown in Figure 30.…”
Section: Infrared (Ir) Absorption Raman Scattering and Refractive Imentioning
confidence: 99%
“…The general procedure to synthesize the diarylethene-based polyurethanes consists of the reaction between the specific photochromic monomer (in a 50% ratio on the total OH groups, which corresponds to about 40 wt % of all components), polyols, and 4,4 -diisocyanate dicyclohexylmethane (H12MDI), as described in the literature [14].…”
Section: Polyurethane Productionmentioning
confidence: 99%
“…In particular, it has been shown that polyurethanes are good candidates, showing good resistance to solvents and allowing for versatile polymerization and processing. Moreover, polyurethanes (PUs), allowed for tunable properties, and high contrast of the processed films [14].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting strategy is the development of photochromic polymers, where the active unit is directly linked to the main polymer chain [18][19][20][21][22]. In this way, the very high concentration of active units in the material generates high optical responses with very thin films (in the order of 1 ÎŒm) [22].…”
Section: Photochromic Materials and Photoconversion Modelmentioning
confidence: 99%